Corporate Culture and Organizational Change- a Study on a Large Pharmaceutical Company in Bangladesh - Ahsan, S.M. Rezaul (Asian Business Review, 2014)
This paper investigates the relationship between corporate culture and attitudes toward organizational change from the perspectives of a large pharmaceutical company in Bangladesh. A structured questionnaire was developed on the basis of the competing values framework of culture typology of Cameron and Quinn (2006) and a study of Justina Simon (June 2012), which was distributed to the 55 staff members of the company. The result shows that there is a significant relationship between corporate culture and organizational change. The study reveals that the organization has adopted all four types of organizational culture and the dominant existing organizational culture is the hierarchy culture. The study also shows that the resistance to change is a function of organizational culture. The implications of the study are also discussed.